Obesity Kuznets Curve conjecture assessment in African economies: conditioning effects of urbanization, food, and trade using gender-based regional analysis - Wenxin Wang; Isaac Adjei Mensah; Samuel Atingabili; Akoto Yaw Omari-Sasu; Emmanuel Nouwati; Clement Yenube Kunkuaboor; Emma Serwaa Obobisa; Mu Qiao (Globalization and Health)
Abstract Background Obesity is recognized as a significant health challenge in Africa, contributing to the double burden of malnutrition and elevating the risks of diabetes, heart disease, and hypertension. Existing studies on the Obesity Kuznets Curve (OKC) assessment overlook Africa’s unique socio-economic and gender-specific dynamics. In light of the claim that different socioeconomic characteristics significantly influence the prevalence of obesity in different nations, this study examines the nonlinear relationship between economic growth and each of the obesity prevalence in males, females, and both sexes, respectively, while accounting for the effects of urbanization, trade, and food production. Methods The study employs a panel data design to analyse the OKC hypothesis in a multivariate non-linear framework. The study focusses on Africa, with the study units consisting of African countries analysed within the framework of regional groupings and differentiated by obesity prevalence in males, females and both sexes correspondingly. Specifically, the study utilised panel data of 45 African nations sub-panelled into Eastern, Western, Central and Southern regions during the period from 2000 to 2020. The primary outcome variable is obesity prevalence, while the key exposure variable is economic growth. The study also considers trade openness, urbanization and food production as additional covariates influencing obesity prevalence to provide a nuanced analysis. Considering the existence of residual cross-sectional dependence and heterogeneity issue in the panel data, we applied the novel Bias-Corrected Method of Moments estimator using the dynamic fixed-effect model as the main method to ensure robust and reliable estimates. This novel approach allows the study to address unobserved heterogeneity and interdependencies across regional economies. Results The principal findings demonstrated a distinct pattern of the OKC (non-linear relationship between the country’s economic growth and obesity) when analysing prevalence of obesity in both sexes collectively and also when considering obesity prevalence in males and females separately across the geographical panels used. The results further showed that trade openness is positively associated with obesity prevalence in males and females separately together with both sexes collectively across all regional classifications. However, the effect of urbanization, and food production on obesity prevalence in males, obesity prevalence in females and obesity prevalence in both sexes correspondingly varied across the regional classifications. Conclusion Our analysis leads to specific policy recommendations, including the development of robust, regionally tailored health policies aimed at preventing obesity across Africa. These include promoting healthy diets through subsidies on nutritious foods, regulating trade polices to limit unhealthy food imports and integrating urban planning to encourage active lifestyles. Considering the rapid economic expansion, urbanization, trade liberalization and food production in many African nation, these strategies ought to address regional and gender-specific dynamics while aligning with global development goals such as SDG 3 (good health and well-being) and SDG2 (zero hunger), to effectively mitigate the rising prevalence of obesity.